Activation of Nrf2 might reduce oxidative stress in human granulosa cells. (15th July 2018) - Akino, Nana; Wada-Hiraike, Osamu; Terao, Hiromi; Honjoh, Harunori; Isono, Wataru; Fu, Houju; Hirano, Mana; Miyamoto, Yuichiro; Tanikawa, Michihiro; Harada, Miyuki; Hirata, Tetsuya; Hirota, Yasushi; et al.
Abstract: Nuclear factor-E2-related factor 2 (Nrf2)/Kelch-like ECH-associated protein 1 (Keap1)-antioxidant response element (ARE) signaling pathway is one of the most important defense mechanisms against oxidative stress (OS). It is well documented that equilibration status of OS plays fundamental roles in human reproductive medicine, and the physiological role of Nrf2 in ovarian granulosa cells (GCs) has not been determined yet. Herein we aimed to study the function of Nrf2 in GCs. Human ovarian tissues were subjected to immunohistochemistry to localize Nrf2 and Keap1 and we detected the expression of Nrf2 and Keap1 in the human GCs. Human luteinized GCs were isolated and cultured, and hydrogen peroxide (H2 O2 ) or Dimethylfumarates (DMF), an activator of Nrf2, were added to GCs to analyze the relationship between Nrf2 and antioxidants by quantitative RT-PCR. The mRNA levels of Nrf2, catalase, superoxide dismutase 1 (SOD1), and 8-Oxoguanine DNA glycosylase (OGG1) were elevated by H2 O2, and DMF treatment showed similar but pronounced effects through activation of Nrf2. To determine the relationship of Nrf2 and the generation of antioxidants, siRNAs were used and quantitative RT-PCR were conducted. Decreased expression of Nrf2 resulted in a decreased level of these antioxidant mRNA. Intracellular levels of ROS were investigated by fluorescence of 8-hydroxy-2′-deoxyguanosine and fluorescent dye, 2′, 7′-dichlorodihydrofluorescein diacetate after H2 O2 and/or DMF treatment, and DMF treatment quenched intracellular ROS generation by H2 O2 . These results show that activation of Nrf2 might lead to alleviate OS in human GCs, and this could provide novel insight to conquer the age-related fertility decline that is mainly attributed to the accumulation of aberrant OS. Highlights: Activation of Nrf2 leads to alleviate oxidative stress in human granulosa cells. Activation of Nrf2 mainly results in the generation of antioxidants and cytoprotective factors. Dimethylfumarates quenched intracellular reactive oxygen species generation.